Effects of the COVID Situation on Thai Education Management: Alternative Education is the Main Way and the way to Survive Thai Education in the Future - Thumthong, Boonleang; Vannit, Pratoun (Dhammathas Academic Journal, 2022)
Positive impact on learning management in the situation of COVID - 19, it was found that educational institutions have changed their plans and goals in educational management. The Internet network system has been improved to be of higher quality. New learning management styles and technologies are used to make learning management more interesting. And new methods of measurement and evaluation are increasingly used. The students spend more time with their families. Students can reduce the time, risk and cost of commuting to school. The negative impact on the learning management system in the educational institutions was found that the internet network and communication are insufficient and the signal is unstable. The quality of teacher learning management declined. It is a workload and affects the time of teaching and learning. Teachers are concerned about the new learning arrangements. And the student’s academic performance will decline. Alternative education is another approach to education that focuses on the learner as a very important aspect. It pays attention to age, gender, race, religion, values, beliefs, aptitudes, readiness and interests, including the environment, community context, wisdom, knowledge and arts and culture in the locality where the learners live. Therefore, learners have the opportunity to truly study according to their own potential. It is one of the important guidelines that can be a solution to Thailand’s educational problems in the future due to the COVID-19 outbreak affecting education around the world.